ANALISIS EFEKTIVITAS PROGRAM KEMITRAAN SEBAGAI WUJUD TANGGUNG JAWAB SOSIAL (CSR) PADA UMKM BINAAN PT KERETA API INDONESIA (PERSERO) DAERAH OPERASI 4 SEMARANG - Trya Utari Kurniasih; Rodhiyah Rodhiyah (Universitas Diponegoro, 2016)
PT. KAI (Persero) is a state that the obligation to conduct social responsibility (CSR) to the public one of which is to participate actively provide assistance to small businesses through the Partnership Program which provides additional capital loans. What is interesting is the implementation that is still less than the maximum management. The purpose of this study was to determine the effectiveness of the implementation of the Partnership and determine the impact on the effectiveness of SME Patronage. Descriptive qualitative research with case studies. Methods of data collection that structured interviews, observation and documentation. Determination of informants using purposive sampling technique. Informants in this study amounted to 11 people, one person in charge of the Partnership and 10 SMEs consisting of industry, trade and services. Discussion of the results shows the implementation of the partnership program has not been effective, determination SME Patronage most families KAI employees, not their coaching and monitoring shows that the partnership program has not led to the development of business resulting in less impact signifikasn to increase the effectiveness of SME Patronage. Yet most get the loan amount in accordance with the proposed, did not take long to get the disbursement of funds as well as most small businesses pay the installments on time. The partnership program has an impact on increasing the quantity of goods and service quality, satisfaction and motivation, revenue and profit, although not significant, and the improvement of equipment, machinery and raw materials. Advice writer is the establishment of the CSR division so that there is coaching, training and monitoring to MSMEs.